Numerical modelling of brittle fracture using lattice particle method with applications to fluid structure interaction problems via SPH coupling - Ng, Khai Ching; Chen, Hailong (Elsevier, 2023)
This paper presents an improved failure model for simulating brittle fracture using the mesh-less Lattice Particle Method (LPM). By modelling the initial crack line using the Remove Bond (RB) approach as outlined in this paper, a new formulation is then developed for predicting the mode-I Stress Intensity Factor (SIF) near the crack tip. Compared to the conventional Remove Particle (RP) approach, it is found that the accuracy of the present SIF formulation based on the RB method is superior. A series of benchmark test cases are simulated to test the numerical accuracy and numerical convergence of the method. Finally, the LPM method is coupled with the Smoothed Particle Hydrodynamics (SPH) method for studying Fluid Structure Interaction (FSI) problems involving solid fracture and free surface.